Atividade potencialmente alelopática do óleo essencial de Ocimum americanum - SOUZA FILHO, Antonio Pedro da Silva (2013)
Essential oils are known for their several biological activities. The biodiversity of the Amazon region is rich in essential-oil producing plants.The aim of this work was to study the potentially allelopathic activity of the essential oil of Ocimum americanum and to determine its effects on seed germination and growth of two weed species. Solutions of the essential oil were tested at concentrations varying from 100 to 2,000 mg L-1, considering their effects on seed germination (at 25 ºC and a photoperiod of 12 hours) and radicle and hypocotyl growth (at 25 ºC and a photoperiod of 24 hours) of the weeds Mimosa pudica and Senna obtusifolia. Factors related to concentration, specificity of the receiving plants and the parameters analyzed were decisive for the effects obtained. Overall, there was a positive relation between concentration and inhibitory effect. M. pudica tended to be more sensitive to the effects than S. obtusifolia. Seed germination was more affected by the essential oil, followed by radicle elongation and hypocotyl elongation. The observed effects can be attributed to the composition of the essential oil, that includes monoterpenes, sesquiterpenes, aliphatic compounds and phenylpropanoids. The compounds limonene, camphor and linalol, found in the essential oil, are known to have allelopathic activity.